Emerging Technologies for Autonomous Language Learning: Using Pre-Writing Tool for ESL - Ainil Sulaiman, Nur; Md Yunus, Melor; Hashim, Harwati; Noor Azilah, Siti; Kamilia, Fatin; Zaireen, Natasha (International Journal of Engineering and Technology, 2018)
The rapid development of the technology has shifted the way how the student learns and how teacher teaches. Social media such as Pinterest may not only provide opportunities to achieve social function, but also create positive learning environment for the students. It also has become an alternative tool to teach writing. This paper aims to investigate students’ perceptions on using Pinterest as ESL pre-writing strategy. It also attempts to identify advantages and challenges that students faced when using Pinterest as pre-writing strategy to enhance ESL writing. The respondents of the study consisted of 50 Form Five secondary school students from Menara Gading Academy located at Kuantan, Pahang. The findings revealed that the respondents showed positive feedback to the integration of Pinterest as a pre-writing tool to learn ESL writing. Pinterest also help to expand and organise ideas for writing and inject the fun element in learning due to its easy, friendly and interesting features.  However, the respondents in opinion that they can be easily carried away by Pinterest and lost focus in the learning process. Unable to secure internet connection would be biggest hurdle to implement Pinterest in a classroom setting.